S96 Survival after the first myocardial infarction is shorter in patients with COPD compared to the general population. (2nd December 2011) - Quint, J K; Herrett, E; Timmis, A; Hemingway, H; Smeeth, L
Abstract : Background: Patients with COPD are at increased risk of myocardial infarction (MI) compared to the general population and have shorter survival after any MI. We investigated whether this held true in patients with an "unanticipated" MI, defined as an MI occurring as the first manifestation of atherosclerotic disease and without any traditional cardiovascular risk factors and without any prior chest pain. Methods: All patients experiencing their first MI between 1st January 2003 and 31st December 2008 as recorded in Myocardial Ischaemia National Audit Project (MINAP), who had no previous evidence of MI in their General Practice Research Database (GPRD) or MINAP record were included. Patients under 18 years of age, not registered with GPRD at the time of MI, or with <1 year of standard follow-up before their MI were excluded. Data were provided by the "Cardiovascular Disease Research Linking Bespoke Cohorts and Electronic Records" (CALIBER) group at UCL. The primary exposure of interest was diagnosis of COPD (defined in GPRD) and the outcome death after MI. Survival analysis was done using Kaplan–Meier methods. Cox proportional hazards models were used to adjust for potential confounders (age and sex). Results: 8065 individuals were included, 968 (12%) of whom had a physician diagnosis of COPD made either before the first MI or during the follow-up period. 87 patients died on the day of admission 10 (11.5%) of whom had COPD. The overall mortality rate was 160.2 deaths (95%CI 145.5 to 176.5) per 1000 person years in those with COPD compared to 99.4 deaths (95.2 to 103.9) per 1000 person years in those without COPD. After adjusting for confounding by sex and stratifying for age, survival was shorter after 1st MI in patients with COPD; HR 1.37 (1.23 to 1.52, p<0.001) in those with COPD compared to those without COPD (Abstract S96 figure 1 ). Survival was shorter in those (n=96) who exacerbated within 6 months of their 1st MI; HR 1.72 (1.13 to 2.60, p=0.01). Conclusions: Survival is shorter after an "unanticipated" MI in patients with COPD and patients who exacerbate within 6 months of their MI have an even higher mortality rate.